Electrically Tunable Propagation Properties of the Liquid Crystal-Filled Terahertz Fiber - Wang, Doudou; Mu, Changlong; Li, Baihong; Yang, Jing (Applied sciences, 2018)
A bandgap-guiding microstructured fiber for terahertz (THz) radiation was designed by infiltrating the cladding air holes with nematic liquid crystal. Structural parameter dependence of the photonic bandgaps, polarization-dependent bandgap splitting, and electrically tunable propagation properties of the designed fiber were investigated theoretically by using the finite-element method. An external electric field applied across the designed fiber can broaden the effective transmission bandwidth and achieve single-mode single-polarization guidance. Flattened near-zero group-velocity dispersion of 0 ± 1 ps/THz/cm was obtained for the y-polarized fundamental mode within a broad frequency range. Our results provide theoretical references for applications of liquid crystal-filled microstructured fiber for dynamic polarization control and tunable fiber devices in THz frequency.